Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Đặt:
\(\dfrac{a}{c}=\dfrac{c}{b}=k\Rightarrow\left\{{}\begin{matrix}a=ck\\c=bk\\a=bk^2\end{matrix}\right.\)
\(\dfrac{a}{b}=\dfrac{bk^2}{b}=k^2\)
\(\dfrac{a^2+c^2}{b^2+c^2}=\dfrac{ck^2+bk^2}{b^2+c^2}=\dfrac{k^2\left(c^2+b^2\right)}{b^2+c^2}=k^2\)
\(\Rightarrow\dfrac{a}{b}=\dfrac{a^2+c^2}{b^2+c^2}\)
\(\Rightarrowđpcm\)
Tương tự
\(\frac{a}{c}=\frac{c}{d}=>\frac{a^2}{c^2}=\frac{c^2}{b^2}\)
áp dụng t/c dãy tỉ số bằng nhau ta có:
\(\frac{a^2}{c^2}=\frac{c^2}{b^2}=\frac{a^2+c^2}{c^2+b^2}\)
\(\frac{a}{c}=\frac{c}{b}=>\frac{a^2}{c^2}=\frac{a}{c}\cdot\frac{a}{c}=\frac{a}{c}\cdot\frac{c}{b}=\frac{a}{b}\left(dpcm\right)\)
Ta có : \(\frac{a}{c}=\frac{c}{b}\)
\( \implies\) \(ab=c^2\)
a)\(\frac{a^2+c^2}{b^2+c^2}=\frac{a^2+ab}{b^2+ab}=\frac{a\left(a+b\right)}{b\left(b+a\right)}=\frac{a}{b}\)
b) \(\frac{b^2-a^2}{a^2+c^2}=\frac{b^2-a^2}{a^2+ab}=\frac{\left(b-a\right)\left(b+a\right)}{a\left(a+b\right)}=\frac{b-a}{a}\)